Viroid replication: equilibrium association constant and comparative activity measurements for the viroid-polymerase interaction. - Goodman, T C (1984)
The binding and replication of purified potato spindle tuber viroid (PSTV) by DNA-dependent RNA polymerase II from wheat germ was studied in analytical ultracentrifugation experiments and in vitro transcription assays. The equilibrium association constant for the viroid-polymerase interaction is 1.9 X 10(7) M-1. Both ultraviolet and fluorescent monitoring during the sedimentation experiments showed two distinguishable viroid-polymerase complexes. These are interpreted as resulting from a 1:1 and 2:1 enzyme-to-viroid binding stoichiometry. A265/A280 ratios across the sedimenting boundaries, the sedimentation velocity of the complexes, as well as electron microscopic data support this interpretation. The role of viroid secondary structure in enzyme binding and polymerization is discussed in the light of these results and compared with binding and polymerization data for virusoid RNA, single- and double-stranded RNA, and double-stranded DNA.